Differential Effects of Carbohydrates on Behavioral and Neuroelectric Indices of Selective Attention in Preadolescent Children - Walk, Anne M.; Raine, Lauren B.; Kramer, Arthur F.; Cohen, Neal J.; Khan, Naiman A.; Hillman, Charles H. (Frontiers in Human Neuroscience, 2017)
The importance of breakfast consumption for ideal cognitive performance has received much attention in recent years, although research on the topic has yielded mixed results. The present study utilized event-related brain potentials (ERPs) elicited during a modified flanker task to investigate the neuroelectric implications of receiving different mixed macronutrient beverages after an overnight fast. A repeated measures design was employed whereby preadolescent participants (9-10 years of age) completed cognitive testing while ERPs were collected during two non-consecutive testing sessions, one in which they received one of three treatment beverages consisting of mixed-macronutrient formulations (either Carbohydrate Blend, Sucrose, Maltodextrin) and the other in which they received a placebo drink containing Sucralose. Performance indices, ERPs, and blood glucose were recorded at three time points before the testing session and after the ingestion of each drink. While the behavioral performance indices and N2 results showed some evidence of glucose facilitation, the effects were small and selective. Participants who received the Maltodextrin treatment showed faster reaction times and more stable N2 amplitudes after ingesting the treatment beverage. The most robust effects were seen in the P3 amplitude measurement. Across the three drink groups, participants showed a marked amplitude increase over time after the placebo drink was ingested, although P3 amplitudes remained stable when a carbohydrate treatment drink was ingested. These effects were eliminated when changes in blood glucose was accounted for, suggesting that this neurolectric effects were directly related to glycemic change. These findings suggest that ingestion of carbohydrates after an overnight fast results in changes to the P3 amplitude of the ERP waveform elicited during an attentional inhibition task.